Transport and recycling of radiocesium in the alimentary tract of reindeer - Staaland, Hans; Hove, Knut; Pedersen, Øyvind (Rangifer, 1990)
Transport of radiocesium between the body pools and the alimentary tract was studied in 7 reindeer calves. Comparisons were made between reindeer receiving the Cs- binder Prussian blue (Ammon-ium-ironhexacyanoferrate) and untreated animals. The calves were fed lichens contaminated with 134Cs + 137Cs from the Chernobyl accident (about 10 kBq/day) for 4 weeks. Absorption and secretion of radiocesium, Na and K in the alimentary tract were calculated using 51Cr-EDTA as a reference substance. Thirteen sections of the alimentary tract were sampled and analysed for radionuclides and chemical composition. In 4 animals, feeding with contaminated lichens continued until they were slaughtered, whereas in the 3 others the lichen feeding terminated 4 days before slaughter. The activity concentration of Cs nuclides increased 5-17 - fold from duodenum to the distal colon, whereas the concentration of Na decreased and K remained almost constant. Radiocesium, Na and K were secreted into the rumen, the omasum and the abomasum, whereas Na and K also were secreted into the proximal small intestine. Prussian blue had no effect on Na and K recycling, but the flow of radiocesium from the abomasum to the anus and the fecal excretion increased markedly. In the 3 animals where feeding with contaminated lichens was disconutinued 4 days before slaughter, endogenous Cs was continuously recycled between the body pools and the alimentary tract. The net exchange of radiocesium between body pools and the alimentary tract was more than 4 times the amount ingested when lichens were fed. It is concluded that radiocesium is rapidly recycled between the alimentary tract and the other body pools. Cs-binders like ammonium-ironhexacyanoferrate may bind both endogenous Cs and Cs from feed.